An Anatomy of Terror : A History of Terrorism - Sinclair, Andrew 1935- (London Macmillan, 2003)
"Andrew Sinclair's unique history of terrorism explores the methods and thinking behind terrorism and shows how the nature of terror has not changed since the days of the Assassins and the Mongol hordes. The only difference is that modern technology can kill in tens of millions rather than the tens of thousands the horror tactics of antiquity managed."--Jacket.
Include Notes and Index
Keywords: Terrorism -- Terrorism -- History